ANALISIS EFISIENSI ALOKASI FAKTOR PRODUKSI PADA USAHATANI PADI SAWAH DI DESA WULLA KABUPATEN SUMBA TIMUR - Andro Umbu Kaba; Febyningsi Rambu Ladu Mbana (Universitas Garut, 2026)
Examining how production factors and utilisation capacity affect paddy farming in Wulla Hamlet, East Sumba Regency is the primary objective of this research. The methodology involved surveying 78 farmers and analysing their production using multiple linear regression and Cobb-Douglas. Utilisation capacity was measured by the NPMx/Px ratio. The results demonstrate that various aspects of production significantly affect production all at once. Fertiliser, pesticides, and productivity are not major factors; however, land area and seeds do play a role. The form can understand 51.6% of changes in production, according to the R² figure of 0.516. The utilisation of production aspects is not optimal, as revealed by the capacity analysis. The utilisation of seeds, fertilisers, pesticides, and productivity (NPMx/Px < 1) is excessive, while there is still a need to increase land area (NPMx/Px > 1). If farmers want to boost their capacity and income, they need to change the way they use inputs.